Metabolism and ecological niche of Tetrasphaera and Ca. Accumulibacter in enhanced biological phosphorus removal. (1st October 2017) - Marques, Ricardo; Santos, Jorge; Nguyen, Hien; Carvalho, Gilda; Noronha, J.P.; Nielsen, Per Halkjær; Reis, Maria A.M.; Oehmen, Adrian
Abstract: Tetrasphaera and Candidatus Accumulibacter are two abundant polyphosphate accumulating organisms in full-scale enhanced biological phosphorus removal (EBPR) systems. However, little is known about the metabolic behaviour and ecological niche that each organism exhibits in mixed communities. In this study, an enriched culture of Tetrasphaera and Ca. Accumulibacter was obtained using casein hydrolysate as sole carbon source. This culture was able to achieve a high phosphorus removal efficiency (>99%), storing polyphosphate while consuming amino acids anaerobically. Microautoradiography and fluorescence in situ hybridisation confirmed that more than 90% Tetrasphaera cells were responsible for amino acid consumption while Ca. Accumulibacter likely survived on fermentation products. Tetrasphaera performed the majority of the P removal (approximately 80%) in this culture, and batch tests showed that the metabolism of some carbon sources could actually lead to anaerobic orthophosphate (Pi) uptake (9.0 ± 2.1 mg-P/L) through energy generated by fermentation of glucose and amino acids. This anaerobic Pi uptake may lead to lower net Pi release to C uptake ratios and reduce the Pi needed to be removed aerobically in WWTPs. Intracellular metabolites such as amino acids, sugars, volatile fatty acids and small amines were observed as potential storage products, which may serve as energy sources in the aerobic phase. Evidence of the urea cycle was found, which could be involved in reducing the intracellular nitrogen content. This study improves our understanding of how phosphorus is removed in EBPR systems and can enable novel process optimisation strategies. Graphical abstract: Highlights: A P-removing, enriched Tetrasphaera and Ca. Accumulibacter culture was obtained. Tetrasphaera were mainly responsible for amino acid biodegradation and P removal. Tetrasphaera are capable of anaerobic P uptake through energy from fermentation. Numerous intracellular metabolites were identified - could serve as storage products. Improved metabolic understanding could help optimise EBPR systems.